Study of base pressure behavior in a suddenly expanded duct at supersonic mach number regimes using statistical analysis - Quadros, Jaimon Dennis; Khan, Sher Afghan; Antony, A J (Scientific Research of the Institute of Mathematics and Computer Science, 2018)
The present experimental evaluation deals with the behavior of base pressure (BP) in a suddenly expanded duct at supersonic Mach number regimes. The experiments have been conducted for two cases viz. Without and with the use of microjets or active control. The plan of experiments was planned as per the Taguchi design of experiments for acquiring data in a controlled manner. An L27 orthogonal array and analysis of variance (ANOVA) has been employed to investigate the contribution (in terms of percentage) of distinct process parameters like Mach number (M), Nozzle Pressure Ratio (N), Area Ratio (A) and their interactions affecting base pressure. The correlation between these parameters affecting base pressure has been obtained using multiple linear regression analysis. It has been concluded that the Mach number and area ratio were the factors that had high statistical significance on the behavior of base pressure for both cases. The performances of the developed linear regression models have been validated for accuracy prediction by use of 15 test cases. The performance of both the base pressure models was found to be better with percentage prediction in deviation lying in the range of –12.92% to +15.88% for base pressure without control and –10.27% to +19.23% for base pressure with control.